Research in history - Chaturvedi, D. D. 1936- (New Delhi : Anmol Publications, 1995)
Bibliography of Ph. D. and D. Litt. thesis awarded by Indian universities in department of history.
Includes index.
Keywords: Dissertations, Academic -- India -- Bibliography; India -- History -- Bibliography